(untitled) (Nigerian Journal of Technology, 2017)
Most industrial loads are inductive in nature and therefore absorb Volts Ampere Reactance (VARs) leading to lagging power factor. Some inductive loads also produce current and voltage signals with frequencies in integer multiples of the 50 or 60 Hz fundamental frequencies called harmonics. Harmonics in power system causes several problems ranging from overheating, premature equipment failure, false tripping of protective relays resulting in unnecessary down time in industrial production. This work compared the use of series and parallel resonant harmonic filters in suppressing harmonics using Simulink model of the power system of NICHEMTEX, a Textile industry in Nigeria as a case study. Mathematical analysis representing current harmonics distributions on industrials loads with and without capacitor banks were presented. From the analysis, series resonant filter mitigated the total harmonic distortion from 30.080% to 3.460%. The installation of capacitor bank along with the series resonant filter in the industrial facility, further reduced the total harmonic distortion to 0.001% and power factor compensated from 0.860 to 0.894.However, the use of parallel resonant filter mitigated the harmonic distortion to 8.107% and a reduction in the power factor from 0.860 to 0.840. With the parallel resonant filter connection with the capacitor bank, harmonic distortion was mitigated to 0.140%, and the power factor reduced to 0.553, the value which is very low. Hence, it is observed that for this sample case, the use of series resonant filter mitigated the harmonics distortion and maintained power factors within the acceptable IEEE standard values. http://dx.doi.org/10.4314/njt.v36i2.37